Challenging behavior of nursing home residents during COVID-19 measures in the Netherlands. (3rd July 2021) - Leontjevas, Ruslan; Knippenberg, Inge A. H.; Smalbrugge, Martin; Plouvier, Annette O. A.; Teunisse, Saskia; Bakker, Christian; Koopmans, Raymond T. C. M.; Gerritsen, Debby L.
Abstract: Objectives: From the perspective of the nursing home (NH) practitioners, to gain understanding of (1) whether challenging behavior in NH residents changed during the COVID-19 measures, (2) whether the practitioners' involvement in the treatment of challenging behavior changed, (3) what can be learned from the experience of NH staff. Methods: A mixed methods study with a survey in 323 NH practitioners (psychologists, elderly care physicians, nurse practitioners) in the Netherlands, and in-depth interviews in 16 NH practitioners. Nonparametric analyses were used to compare estimated proportions of residents with increased and with decreased challenging behavior. Content analyses were conducted for open-ended questions and in-depth interviews. Results: Participants reported changes in challenging behavior with slightly higher proportions for increased (Q1/Mdn/Q3: 12.5%, 21.7%, 30.8%) than for decreased (8.7%, 14.8%, 27.8%, Z = –2.35, p = .019) challenging behavior. Half of the participants reported that their work load increased and work satisfaction worsened during the measures. Different strategies were described to respond to the effects of COVID-19 measures, such as video calls, providing special areas for residents to meet their loved ones, adjusting activities, and reducing the exposure to negative news. Conclusions: Because COVID-19 measures resulted in both increased and decreased challenging behavior in NH residents, it is important to monitor for their potential long lasting effects. Increased work load and worsened work satisfaction of the NH staff, together with the changes in type of challenging behavior, indicate that the harmful effects of the anti-pandemic measures should be taken seriously.